Psychological Empowerment Link Using Employee Performance and Organizational Commitment on the Generation Gap: PLS-MGA Analysis - IBRAHIM, NURSHAHIRA; Mohamad, Nur Izzaty; Farinordin, Farah Ayuni; Mohd Soffian Lee, Umi Hamidaton; Ismail, Azman (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
The generation gap is critical, especially when employees do not agree about some terms that affect their completion of tasks. This issue is debated in organizations, causing incompatibilities between human resource management and development structures. Hence, these constraints led this study to measure the differences shown by generations X and Y, and how they impact the relationship between psychological empowerment, employee performance, and organizational commitment. This research used questionnaires and in-depth interviews as the main procedures for collecting and obtaining data—196 items of data were received from the Malaysian Islamic Finance Agency. SmartPLS software was used to test the research hypotheses and the differences between the two groups are Gen X and Y (PLS-MGA). The results of the PLS-MGA test confirmed that, in the relationship of psychological empowerment and job performance alone, it was found there was a generational difference between X and Y (p-value < 0.05). However, while running the hypothesis test (using the bootstrapping test), it was found that both hypotheses are acceptable, which shows the relationship between psychological empowerment and job performance based on two different groups, namely Gen Y = t-statistic (10.961) and Gen X = t-statistic (11.993). Thus, H1 is supported. Meanwhile, the relationship between psychological empowerment and organizational commitment is based on two different groups, namely Gen Y = t-statistic (8.675) and Gen X = t-statistic (8.349), which means H2 is also supported. Consequently, it is hoped that the findings of this study will serve as essential guidance for employers in both the public and private sectors. Human resource management teams can use the findings to understand the natural complexity of psychological empowerment constructs in realizing the challenges and difficulties in predicting organizational goals, in terms of job performance and organizational commitment.